Changes in life satisfaction during the transition to retirement: findings from the FIREA cohort study - Prakash K. C.; Virtanen Marianna; Törmälehto Soili; Myllyntausta Saana; Pentti Jaana; Vahtera Jussi; Stenholm Sari (SPRINGER, 2025)
Life satisfaction is an essential construct of well-being that is tied to behavioral, emotional, social and psychological outcomes. This study aimed to examine changes in total and domain-specific life satisfaction during the retirement transition and additionally examine whether those changes differ by gender, occupation, health and spousal working status. Aging public sector employees (n = 3543) from the Finnish Retirement and Aging Study cohort study were followed up annually before and after retirement. Total life satisfaction score (range 4-20) was computed by summing up the responses in four domains (interestingness, happiness, easiness and togetherness). The mean and mean change estimates and their 95% CI were calculated by using the linear regression models with generalized estimating equations, adjusted for age, gender, occupation, health and marital status. Total life satisfaction score improved among the entire study population during the retirement transition and remained stable thereafter. The improvement was greater among women versus men (gender * time interaction p = 0.004), among those with suboptimal health before retirement vs. those who had good (health * time p < 0.0001) and those who had no spouse vs. those who had a retired or working spouse (spousal-status * time p < 0.0001). In case of domain-specific life satisfaction scores, the greatest improvement was observed in the easiness domain. Life satisfaction improves during the retirement transition period, especially among women, those with suboptimal health and those living without a spouse. The improvement was considerably greater in the easiness domain than any other domains. Life satisfaction remained improved and stable during the post-retirement period.